As ferramentas de rastreabilidade e a gestão hospitalar: a percepção da eficiência e da eficácia em hospitais do município de São Paulo - Vidal, Emerson Pessoa [UNIFESP] (2020)
Introduction: Our society has advanced in terms of technology and health could not be different. Despite the benefits and advantages that such improvements entail, it is not yet known what contributions have been added to the hospital environment, and whether such technological engineering has managed to generate value and adapted to different factors within the professional culture of such institutions, in order to establish relevance. Still, the use of tools can be conditioned to the view that the managerial sectors have of such instruments and its widespread use can be intrinsically related to the base of utilitarian nature. Objectives: The work aims to identify and understand the perception that health managers have of traceability tools such as bar codes, radio frequency identification technology, card technology, among others, and their view on their efficiency, efficacy and effectiveness on the hospital environment. Thus, it is recommended investigating the relationship that hospital managers maintain with the tools and with their daily and routine use (when applicable). Method: Through Likert questionnaires, the work seeks to analyze the perception of managers of large and special hospitals, and by means of descriptive and statistical treatment seeks to distinguish the factors that contribute to efficiency, efficacy and effectiveness if and when there is within the hospital context. Results: The results direct us to the fact that the traceability tools have a significant expression in the hospital context, contributing to efficiency, efficacy, and effectiveness. The data also reveal that the longer the tool is used, the greater the results, and that the nonadoption by most hospitals are due to the fact that unusual policies are rarely applied. The profile reveals that of the hospitals participating in the research, a significant percentage make continuous use of traceability tools. Conclusions: The improvement of the efficiency, effectiveness and effectiveness of a hospital institution depends, among other things, on technologies such as the traceability tools that show to be significantly expressive when it comes to raising the quality of the institutional framework. Thus, no matter how much the human being works within a methodological rigor, it is still flawed and for that very reason needs contextual conditions that raise the quality and coordination of tasks.